The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ecs2.1485
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of tree and stand properties in susceptibility to spruce beetle outbreak in the mid‐20th century

Abstract: Citation: Bakaj, F., N. Mietkiewicz, T. T. Veblen, and D. Kulakowski. 2016. The relative importance of tree and stand properties in susceptibility to spruce beetle outbreak in the mid-20th century. Ecosphere 7(10):e01485. 10.1002/ecs2.1485Abstract. Tree susceptibility to potentially lethal agents is determined not only by attributes of individual trees, but also by neighborhood effects at a range of scales. For example, effects of disturbances on individual trees are often contingent on the size, configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
6
16
0
Order By: Relevance
“…Although most evidence suggests that surface air temperatures are the predominate influence on spruce beetle dynamics, drought stress should not be dismissed entirely as a determinant in patterns of outbreak initiation and progression at certain scales, particularly when interacting with stand structure. Indeed, a number of other studies on spruce beetle mortality have investigated how certain aspects of stand structure have affected percentage mortality across landscapes (e.g., Bakaj, Mietkiewicz, Veblen, & Kulakowski, 2016; Doak, 2004; Hart, Veblen, & Kulakowski, 2014; Temperli et al., 2014). These studies have largely found tree size to be the best predictors of tree mortality, whereas stand structure has been of lesser importance (Bakaj et al., 2016; DeRose & Long, 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most evidence suggests that surface air temperatures are the predominate influence on spruce beetle dynamics, drought stress should not be dismissed entirely as a determinant in patterns of outbreak initiation and progression at certain scales, particularly when interacting with stand structure. Indeed, a number of other studies on spruce beetle mortality have investigated how certain aspects of stand structure have affected percentage mortality across landscapes (e.g., Bakaj, Mietkiewicz, Veblen, & Kulakowski, 2016; Doak, 2004; Hart, Veblen, & Kulakowski, 2014; Temperli et al., 2014). These studies have largely found tree size to be the best predictors of tree mortality, whereas stand structure has been of lesser importance (Bakaj et al., 2016; DeRose & Long, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of other studies on spruce beetle mortality have investigated how certain aspects of stand structure have affected percentage mortality across landscapes (e.g., Bakaj, Mietkiewicz, Veblen, & Kulakowski, 2016; Doak, 2004; Hart, Veblen, & Kulakowski, 2014; Temperli et al., 2014). These studies have largely found tree size to be the best predictors of tree mortality, whereas stand structure has been of lesser importance (Bakaj et al., 2016; DeRose & Long, 2012b). Our study confirms that large trees tended to die earlier in the outbreak, signaling beetles preferred these large trees (Appendix S1: Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial attributes of the neighborhood surrounding a host tree, in addition to characteristics of the tree itself, can also influence susceptibility to bark beetle attack (Bakaj et al 2016). For example, while large diameter host trees are preferentially attacked during an outbreak, small diameter host trees may also be attacked when in close proximity to large diameter host trees (Preisler and Mitchell 1993, Kashian et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further, prevalence and basal area of beetle‐killed host trees may be greater in denser neighborhoods or clusters within a stand (Olsen et al 1996, Negrón et al 2001). Fine scale neighborhood effects are expected to be secondary to tree scale characteristics in determining host tree susceptibility to bark beetle outbreak (Bakaj et al 2016). However, it remains unclear how tree neighborhood characteristics might mediate individual host tree susceptibility, and whether these effects vary with tree size.…”
Section: Introductionmentioning
confidence: 99%
“…Variety across landscapes is also created in areas disturbed by snow avalanches, which can create fire breaks (Veblen et al 1994). Wildfires may reduce susceptibility to spruce beetle (Dendoctronus rufipennis) outbreaks by reducing large Engelmann spruce trees (Bakaj et al 2016).…”
Section: Factors That Enhance Resilience To Nonclimate Stressorsmentioning
confidence: 99%